PERAN BPOM SEBAGAI UPAYA PERLINDUNGAN KONSUMEN ATAS HAK INFORMASI YANG JELAS TERHADAP MAKANAN TIDAK BERLABEL OLEH UMKM DI DESA JARIN - Septi, Nurdini Dwi; Soleh, Moh (jurnal.unprimdn.ac.id, 2024)
Edict No. 31, issued in 2018 by the Bureau of Food and Drug Scrutiny, mandates that all consumable items display a vital data label. The National Agency for Food and Drug Supervision (BPOM) is pivotal in advancing micro, small, and medium-sized enterprises (MSMEs) throughout Indonesia. A Distribution Certification granted by BPOM is the primary condition allowing a product to bear the BPOM emblem on its packaging, signaling that the item has undergone a rigorous assessment and holds consumer-safe contents. This badge of approval bolsters public confidence in MSME goods, potentially amplifying their market stance and contributing to MSME economic growth. This research aims to delve into the regulations surrounding labeling food products by MSME operators in Jarin Village.